Clinical characteristics and outcome of critically ill children referred to a tertiary hospital in Indonesia: a prospective observational study - Desy Rusmawatiningtyas; Vicka Oktaria; Antonius H Pudjiadi; Firdian Makrufardi; Job. B.M. van Woensel (BMC, 2024)
Abstract Background The clinical characteristics of pediatric critically ill patients who need referral to a tertiary hospital is often unknown in resource limited settings where constraints in diagnosis capacity, resources, and infrastructures are common. There is a need to increase insight in the characteristics of these patients for capacity building strengthening and appropriate resource allocation. The aim of this study was to describe the clinical characteristics and outcomes of critically ill children who are referred to a tertiary referral teaching hospital in Yogyakarta. Methods A prospective observasional study was carried out from July 1st, 2022 -January 31st, 2023 which included all critically ill pediatric patients who were referred through the Integrated Referral System (SISRUTE) to the Pediatric Intensive Care Unit (PICU) of dr. Sardjito hospital. We excluded patients who were referred with a request for admission to the PICU, but were not admitted to the PICU due to their stable condition and lack of the need for intensive care. Result During the study period, we received 1046 emergency referral requests for pediatric patients via SISRUTE, of those, 562 (53.7%) patients were critically ill. The reasons of PICU referral request were the need of solely intensive care 504 (89.7%), the need of multidisciplinary team care, including intensive care 57 (10.1%) and parents request 1 (0.3%). The pre-referral emergency diagnosis was shock 226 (40.3%), respiratory distress/failure 151 (26.7%), central nervous system (CNS) dysfunction 135 (24.1%), trauma 33 (5.9%) and sepsis 17 (3%). Of the 562 critically ill PICU referral requests, 473 (84.2%) requests were accepted. One hundred and eighty-one (58.7%) patients were finally admitted to the PICU, 125 (40.3%) admitted to our regular ward due to stable condition, 4 (1.3%) patients died in Emergency Departement (ED). The remaining accepted patients on request did not arrive in our facility due to various reasons. The mean (SD) response time was 9.1 (27.6) minutes. The mean (SD) transfer time was 6.45 (4.73) hours. Mean (SD) PICU and hospital length of stay was 6.7 (8.3) days and 10.2 (9.2) days respectively. PICU and hospital mortality was 24.3% and 29.7%, respectively. Conclusion The mortality rate for critically ill pediatric patients referred to a tertiary PICU still high, with shock being the most common pre-referral emergency diagnosis. There is a discrepancy between the referring hospital's and the referral hospital's indication for PICU admission. The time required to reach the referral hospital is quite lengthy.